STRATEGI PEMERINTAH TERHADAP PENGEMBANGAN OBJEK WISATA ALAM DI DESA TANA TORO KECAMATAN PITU RIASE KABUPATEN KABUPATEN SIDENRENG RAPPANG - Hasmiati; Ibrahim, Monalisa; Sapri (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
This research aims to determine the government's strategy for developing natural tourist attractions in Tana Toro village, Pitu Riase subdistrict, Sidenreng Rappang district. The population in this study was 579 people with 85 samples. The research method uses quantitative descriptive, data collection techniques, observation, literature study and questionnaires, the data analysis techniques used are descriptive statistical analysis, data quality testing (validity & reliability testing), simple linear regression analysis and hypothesis testing using the SPSS26.0 application. The results of this research show that 58% of the average percentage of government strategies in Tana Toro village, Pitu Riase subdistrict, Sidenreng Rappang district is in the "poor" category, while the highest indicator is direction, which is 60%, while the lowest indicator is goals, which is 56%. And the results of research related to tourism development of 58% are in the "poor" category, while the highest indicator is attractiveness and tourism organization with the same percentage results, namely 60%, while the lowest indicator is easy to reach at 56%. From the ANOVA test, the Fcount obtained was 900 with a significance level of 0.004 (sig 0.004<0.05), based on the calculated t value > t table or 948 ≥ 1.676, then H0 was rejected, meaning that the Government Strategy is Significant/Influential on the Development of Natural Tourism Objects in the Village Tana Toro, Pitu Riase District, Sidenreng Rappang Regency.